Balloon Dilation of the Eustachian Tube: Early Outcome Analysis. Issue 3 (March 2015) - Gürtler, Nicolas; Husner, Alexander; Flurin, Honegger
Abstract : Objective: To assess Eustachian tube balloon dilation in the treatment of Eustachian tube dysfunction by objective analysis, especially tubomanometry. Study Design: Retrospective cohort study. Setting: Tertiary referral hospital. Patients: Patients undergoing Eustachian tube balloon dilation for treatment of Eustachian tube dysfunction. Intervention: Eustachian tube balloon dilation. Main Outcome Measures: Subjective improvement, otomicroscopic findings, tympanogram, air-bone gap in pure-tone audiogram, R-value in tubomanometry at three pressure measurements (30, 40, and 50 mbar) and the Eustachian Tube Score (ETS). Results: Eustachian tube balloon dilation was performed in 21 patients. The Eustachian Tube Score including the R-values, tympanogram, and air-bone gap all showed a statistically positive outcome ( p < 0.005) after Eustachian tube balloon dilation. Subjective improvement was seen in 76%. Normal R-values were achieved in 57%. Retraction processes of the tympanic membrane improved in 18% of patients. Only one minor bleeding complication occurred. Conclusion: Eustachian tube balloon dilation constitutes a safe and very promising treatment option for patients with Eustachian tube dysfunction based on early-outcome analysis. ETS and specifically tubomanometry appear promising as assessment tools but await validation for use in the diagnostic workup and outcome analysis after ETBD. The pathophysiologic mechanism of Eustachian tube balloon dilation remains unclear. Long-term analysis and stratification of patients are needed to better evaluate the definite value of Eustachian tube balloon dilation.